DUTIES OF ALTAR BOYS AND GIRLS IN THE CELEBRATION OF THE EUCHARIST IN THE LAHEWA PARISH AND THE HATI KUDUS YESUS TELUK DALAM PARISH - Gea, Mawarni; Sihite, Bartolomeus; Luahambowo, Leoni Intan; Zebua, Ribk Yusniat; Lase, Yasman Handayani; Nazara, Imelda Iyun Kristina (International Journal of Artificial Intelligence Research, 2025)
Task altar boys and girls in celebration liturgy Eucharist is Wrong One tasks to be done lived with heart happy . Objective study This For know about task altar boys and girls in celebration Eucharist as well as How understanding for altar boys and girls in operate his duties in accordance with order method And attitude in liturgy Church . Method research used is study qualitative with approach studies case . Election sample in study This use technique purposive sampling . Technique data collection was carried out with technique observation , interview And documentation .  Through learning And the coaching provided to altar boys , they capable operate task with Good . Through the example of Saint Tarcisius , makes altar boys and girls are getting bigger discipline And responsible answer in operate task . Become a altar servers not just For enliven celebration Eucharist but become altar server meaning become waiter Lord And all over people . Become altar boys give impact positive specifically for people teenager Catholic in life daily in develop faith And become means For near with Lord . Although thus , the altar boys still need coaching And teaching specifically so that they the more understand involvement And task they in celebration Eucharist .